Floating islands as phytoremediation for domestic wastewater from the oxidation lagoon in Manabí - Bolívar (Research, Society and Development, 2025)
The main objective of this research was to evaluate the removal efficiency of solids in domestic wastewater from the Bolívar canton using floating islands with three plant species: Dracaena trifasciata, Dracaena sanderiana, and Philodendron cutting. To analyze the potential of each species, phytoremediation treatments were carried out with a hydraulic retention time of 96 hours. The physicochemical analysis of the samples included pH, turbidity, electrical conductivity (EC), and total dissolved solids (TDS). The results revealed that phytoremediation achieved the highest efficiency in turbidity removal, with percentages reaching up to 99%. In contrast, Dracaena trifasciata achieved a removal rate of 75%. These findings highlight the potential of floating islands as an effective and sustainable solution for the treatment of domestic wastewater, varying according to the species used.